Sistem Pendukung Keputusan Pemberian Kredit Kendaraan Menggunakan G2M Weighting dan Metode Comprehensive Distance Based Ranking - Parningotan Simamora; Adhie Thyo Priandika (Bulletin of Computer Science Research, 2025)
Providing vehicle loans is one of the important services in the financing sector that requires an objective and accurate evaluation process of prospective debtors. This research aims to develop a Decision Support System (SPK) that can assist in the selection process of providing vehicle credit by combining the G2M Weighting and Comprehensive Distance-Based Ranking methods. The G2M method is used to objectively determine the weight of criteria based on multi-assessment analysis, while the CDR method is used to conduct alternative rankings based on a comprehensive distance to ideal and non-ideal solutions. The results of the calculation using the comprehensive distance-based ranking method, Gita ranked first with a final value of -0.0098, showing that it has the closest distance to ideal conditions and the furthest from non-ideal conditions compared to other alternatives. In second place is Ahmad with a value of -0.0067, followed by Hadi in third place with a value of -0.0042. The final results show that the combination of these two methods is able to provide effective recommendations in identifying potential debtors who are most deserving of credit, taking into account all assessment criteria in a comprehensive and structured manner. This system is expected to improve decision-making accuracy, speed up the selection process, and minimize the risk of errors in vehicle lending.